Conformational Analysis with Elucidation on Molecular Structure, Electronic Properties, and Reactivity of the Nitroglycerin from DFT - Paneru, Tirth Raj; Tandon, Poonam; Joshi, Bhawani Datt (Journal of Institute of Science and Technology, 2024)
This work involved the use of a one-dimensional potential energy surface scan to investigate the most stable conformer of nitroglycerin through conformational analysis. The goal of this work is to perform a quantum chemical calculation using density functional theory to gain insight onto molecular structure, reactivity, and electronic properties with the most stable structure. The most stable conformer of nitroglycerin was investigated, and its geometrical parameters were compared with experimental values. Non-covalent interaction was also performed, which illustrates the various intra-molecular interactions. The reactive sites were predicted using electrostatic potential surface analysis, with H16 as the best electrophile and N11 as a nucleophile, indicating the location of intermolecular interaction for biological action and crystal packing. The energy gap in the solvent ethanol was determined to be 6.628 eV, while in the gaseous medium; it was 6.684 eV, indicating that nitroglycerin is more reactive and polarizable in the solvent ethanol. A blue shift in the absorption wavelength of UV-Vis spectra was observed by employing time dependent density functional theory with a polarized continuum model in solvent ethanol. The hyperconjugative interactions π(O4-N10)→σ*(O5-N10), σ(O5-N10)→π*(O4-N10), LP(3)O8→σ*(O6-N11), and LP(3)O9→π*(O7-N12) have higher stabilization energy and are crucial to stabilizing the molecule.